Aging behavior of (Cr,Nb)-doped PZT ceramics - P. Ketsuwan (2018)
The aging behavior of 3 mol% Nb 2 O 5 Pb(Zr0.5 2 Ti 0.48 )O 3 with addition of 0.1-3 mol% Cr 2 O 3 prepared via the solid-state reaction technique have been investigated. The aging rate increased with increasing Cr concentration from 0.1 to 0.6 mol%. Further increase in Cr concentration, the aging rate decreased dramatically. From ferroelectric hysteresis loops measurements, the decrease of polarization existed in all of concentrations. © 2013 Copyright Taylor and Francis Group, LLC.